2012
DOI: 10.3109/09513590.2012.730569
|View full text |Cite
|
Sign up to set email alerts
|

Minimal stimulation protocol using letrozole versus microdose flare up GnRH agonist protocol in women with poor ovarian response undergoing ICSI

Abstract: The letrozole/antagonist protocol is a cost-effective and patient-friendly protocol that may be used in poor ovarian responders for IVF/ICSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 30 publications
2
6
1
2
Order By: Relevance
“…In the current study, the number of cancelled cycles in group AL was 2.87 times more than group MF. Despite our study, in the study of Mohsen and El Din, there were no significant statistical difference in the number of oocyte and proper fetus and the number of cancelled cycles between two methods of MF and AL ( Mohsen IA et al, 2013 ). Moreover, in the study of Yarali et al the number of ripe oocyte were significantly higher in MF group, while in their study no significant statistical difference was observed in the number of cancelled cycles between two methods of MF and AL in poor ovarian responders (POR) ( Yarali et al, 2009 ).…”
Section: Discussioncontrasting
confidence: 73%
“…In the current study, the number of cancelled cycles in group AL was 2.87 times more than group MF. Despite our study, in the study of Mohsen and El Din, there were no significant statistical difference in the number of oocyte and proper fetus and the number of cancelled cycles between two methods of MF and AL ( Mohsen IA et al, 2013 ). Moreover, in the study of Yarali et al the number of ripe oocyte were significantly higher in MF group, while in their study no significant statistical difference was observed in the number of cancelled cycles between two methods of MF and AL in poor ovarian responders (POR) ( Yarali et al, 2009 ).…”
Section: Discussioncontrasting
confidence: 73%
“…The results of the two trials with respect to pregnancy rate were totally discordant. Daval (2010)[33] had lower implantation and pregnancy rate in letrozole group, whereas Mohsen and EI Din[34] had similar results between the two groups.…”
Section: Letrozole In Ovarian Stimulation For Ivf/icsimentioning
confidence: 99%
“…Mohsen and El Din [ 23 ] showed no difference in clinical pregnancy rates in poor responders when comparing a GnRHa microflare protocol to a letrozole antagonist protocol; however the days of stimulation and total dose of gonadotropins were significantly lower in the letrozole group. Yarali et al [ 9 ] also studied a microdose GnRH agonist protocol versus a letrozole antagonist protocol in poor responders.…”
Section: Discussionmentioning
confidence: 99%